Factors influence customer preferences on Islamic banking system in Wilayah Persekutuan Kuala Lumpur, Malaysia / Rabiatul Adawiyah Mat Jadi - Mat Jadi, Rabiatul Adawiyah (2011)
The purpose of this study is to investigate the level of customer preferences on Islamic banking system in Kuala Lumpur. This study analyzes and identifies the level and also the relationship of customer preferences toward social and religious perspective, quality of services, confidence and transparency in Islamic banking system. Then, this study also determines the major factor that is reflecting the customer preferences on Islamic banking system. This study done based on the descriptive study as to provide insights and understanding on the factors that influence customer preferences on Islamic banking. This study also uses a sample of 95 respondents in Kuala Lumpur, comprising Muslim and non-Muslim customers. The theoretical framework is modified from Ahasanul Haque et al (2009). The findings of this study show that that the level of customer preferences is moderate and customer preferences has positive and significant relationship with all the variables which are social and religious perspective, quality of services, confidence and transparency in Islamic banking system. Moreover, it also indicates that the most important factor that influences customer preferences on Islamic banking system is social and religious perspective. The major limitation of the paper relates to the size of the sample of respondents and the time constraint.